Recombinant human thrombopoietin prior to mobilization chemotherapy facilitates platelet recovery in autologous transplantation in patients with lymphoma: Results of a prospective randomized study. Issue 3 (September 2021) - Mo, Hongnan; Liu, Peng; Qin, Yan; He, Xiaohui; Han, Xiaohong; Yao, Jiarui; Su, Weicai; Zhang, Shuxiang; Tang, Le; Zhao, Fengyi; Gui, Lin; Yang, Sheng; et al.
Abstract: Background: Chemotherapy plus granulocyte colony-stimulating factor (GCSF) regimen is one of the available approaches to mobilize peripheral blood progenitor cells (PBPCs). It causes thrombocytopenia and delays leukapheresis. This study aimed to evaluate the role of recombinant human thrombopoietin (rhTPO) before mobilization chemotherapy in facilitating leukapheresis in patients with lymphoma. Methods: In this randomized open-label phase 2 trial, patients were randomly assigned in a 1:2 ratio to receive mobilization with rhTPO plus GCSF in combination with chemotherapy (the rhTPO plus GCSF arm) or GCSF alone in combination with chemotherapy (the GCSF alone arm). The recovery of neutrophils and platelets and the amount of platelet transfusion were monitored. Results: Thirty patients were enrolled in this study between March 2016 and August 2018. Patients in the rhTPO plus GCSF arm (n = 10) had similar platelet nadir after mobilization chemotherapy ( P= 0.878) and similar amount of platelet transfusion (median 0 vs. 1 unit, P= 0.735) when compared with the GCSF alone arm (n = 20). On the day of leukapheresis, the median platelet count was 86 × 10 9 /L (range 18–219) among patients who received rhTPO and 73 × 10 9 /L (range 42–197) among those who received GCSF alone ( P= 0.982). After the use of rhTPO, the incidence of platelet count <75 × 10 9 /L on the day of leukapheresis did not decrease significantly (30.0% vs. 50.0%, P= 0.297). Platelet recovery after PBPC transfusion was more rapid in the rhTPO plus GCSF arm (median 8.0 days [95% confidence interval 2.9–13.1] to platelets ≥50 × 10 9 /L vs. 11.0 days [95% confidence interval 8.6–13.4], P= 0.011). The estimated total cost of the mobilization and reconstitution phases per patient was similar between the two treatmtent groups ( P= 0.362 and P= 0.067, respectively). Conclusions: Our findings indicate that there was no significant clinical benefit of rhTPO use in facilitating mobilization of progenitor cells, but it may promote platelet recovery in the reconstitution phase after high-dose therapy. Trial registration: This trial has been registered in Clinicaltrials.gov as NCT03014102.